Relationship between selection criteria and trainee performance in medical specialty training: A retrospective longitudinal study. (19th January 2023) - Jiang, Chali; O'Neill, Brett; Bennett, Haley; Yazdabadi, Anosha
Abstract: Background: Investigation of tools used for candidate selection as predictors of future performance in medical education has been primarily undertaken within the undergraduate setting, but little is known about the selection to medical specialist programs. This retrospective longitudinal study aims to explore correlations between selection tools and the performance of trainees enrolled in the Australasian College of Dermatologists (ACD), the accredited specialist medical college for training in dermatology in Australia. Methods: Data were collected from consecutive cohorts of ACD trainees commencing from 2007 to 2015. Predictive variables were trainee demographics and selection tools (prior academic qualification; research experience; clinical experience; curriculum vitae [CV] rating; interview scores). The outcome variables were exam performance. First Year ([Pharmacology and Clinical Sciences] and Fellowship Exam [Written, Clinical, and Overall Score]). Statistical analyses included: descriptive statistics summaries; bivariate correlation of selection criteria and demographic data with exam performance; and linear regression analysis to identify predictors of exam performance. Results: Demographic analysis ( N = 172) showed that 64% of trainees were female, the average age was 30.5 years (± 3.47) and trainees living in high socioeconomic status (SES) areas were over‐represented. Using Pearson correlation analysis, interview scores were significantly positively correlated with First Year Pharmacology results ( p = 0.018), Fellowship Written results ( p = 0.002), and Fellowship Overall Scores ( p = 0.006). First Year Pharmacology Exam performance was most highly correlated with Fellowship Exam performance ( p = 0.000). No association was identified between exam performance and gender, SES, prior academic qualification, research experience or CV rating. Linear regression analysis showed that interview score ( p = 0.012), entry age ( p = 0.026) and First Year Pharmacology score ( p = 0.002) were predictors of Fellowship exam performance. Conclusion: These results suggest that the comprehensive selection tools used by ACD are effective, with interviews being a highly valid tool linked to exam performance. These findings have important practical implications for assessing the selection process in specialist dermatology training.